Pelanggaran terhadap Akad Mudarabah dalam Perspektif Fikih Mu’amalah (Studi Analisis Kaidah al-Hukmu Yadūru Ma’a ‘Illatihi Wujūdan wa ‘Adaman): Violation of Mudarabah Aqad in the Perspective of Mu’amalah Jurisprudence (Study of the Analysis of the Rules of al-Hukmu Yadūru Ma'a 'Illatihi Wujūdan wa 'Adaman) - Saadal Jannah; Andi Dahmayanti; Windy Sulfiana (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
This study aims to determine the violation of the mudarabah contract in terms of the rules of the proposal of al-hukmu yadūru ma'a 'illatihi wujūdan wa 'adaman). This research uses a type of qualitative descriptive research using normative approach methods and sociological approaches. The results of the study found that violations of the mudarabah contract occur if the contract is not in accordance with the pillars, terms, and conditions that must be in the mudarabah contract, 'Illat in the mudarabah contract includes the perpetrator, the object of the transaction (capital, profit), and the contract (shighat). If the 'illat in the mudarabah contract does not exist, then the contract is haram. The implications of this research are expected to be a reference, reading material that is easy to understand, and become a positive reference material and information to the government entrepreneurs, and society in general.